Penetrative trace fossils from the late Ediacaran of Mongolia: early onset of the agronomic revolution. Issue 2 (28th February 2018) - Oji, Tatsuo; Dornbos, Stephen Q.; Yada, Keigo; Hasegawa, Hitoshi; Gonchigdorj, Sersmaa; Mochizuki, Takafumi; Takayanagi, Hideko; Iryu, Yasufumi
Abstract : The Cambrian radiation of complex animals includes a dramatic increase in the depth and intensity of bioturbation in seafloor sediment known as the 'agronomic revolution'. This bioturbation transition was coupled with a shift in dominant trace fossil style from horizontal surficial traces in the late Precambrian to vertically penetrative trace fossils in the Cambrian. Here we show the existence of the first vertically penetrative trace fossils from the latest Ediacaran: dense occurrences of the U-shaped trace fossil Arenicolites from late Precambrian marine carbonates of Western Mongolia. Their Ediacaran age is established through stable carbon isotope chemostratigraphy and their occurrence stratigraphically below the first appearance of the trace fossil Treptichnus pedum . These Arenicolites are large in diameter, penetrate down to at least 4 cm into the sediment, and were presumably formed by the activity of bilaterian animals. They are preserved commonly as paired circular openings on bedding planes with maximum diameters ranging up to almost 1 cm, and as U- and J-shaped tubes in vertical sections of beds. Discovery of these complex penetrative trace fossils demonstrates that the agronomic revolution started earlier than previously considered.